2014
DOI: 10.4103/0970-9185.125703
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of epidural application of morphine versus gelfoam soaked in morphine for lumbar laminectomy

Abstract: Background:Epidural application of morphine has been used for postoperative analgesia following spine surgery but short duration of action of single application limits its widespread use.Materials and Methods:One hundred and fifty patients undergoing lumbar laminectomy were randomly allocated to two groups of 75 patients each. Anesthetic technique was standardized in both the groups. In Group I, at the completion of laminectomy, a 5 × 1-cm strip of gelfoam soaked in 5 mg morphine (1 mg/ml) was contoured to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 20 publications
0
25
0
2
Order By: Relevance
“…Of the 10 RCTs that studied drugs locoregionally administered to prevent and treat postoperative pain after lumbar spine procedures, 5 tested morphine in various combinations and dosages, 2 tested ropivacaine, 1 tested levobupivacaine, 1 tested fentanyl, and 1 tested MgSO 4 injection . Of the 5 RCTs that tested morphine, morphine administration led to a reduction of analgesic consumption when compared to the control group in 4 studies, while Yen et al found that there was no difference in opioid consumption between extended‐release epidural morphine 10 mg and 15 mg . Ropivacaine effectively reduced pain intensity and proved to be more effective when combined with dexamethasone given caudally than systemic dexamethasone .…”
Section: Resultsmentioning
confidence: 99%
“…Of the 10 RCTs that studied drugs locoregionally administered to prevent and treat postoperative pain after lumbar spine procedures, 5 tested morphine in various combinations and dosages, 2 tested ropivacaine, 1 tested levobupivacaine, 1 tested fentanyl, and 1 tested MgSO 4 injection . Of the 5 RCTs that tested morphine, morphine administration led to a reduction of analgesic consumption when compared to the control group in 4 studies, while Yen et al found that there was no difference in opioid consumption between extended‐release epidural morphine 10 mg and 15 mg . Ropivacaine effectively reduced pain intensity and proved to be more effective when combined with dexamethasone given caudally than systemic dexamethasone .…”
Section: Resultsmentioning
confidence: 99%
“…The sponge is placed over the defect before closure [13]. While Kundra et al compared the effect gelfoam soaked in morphine to direct epidural application of morphine [6] but in these studies morphine was diluted by saline, efficacy and duration of action of morphine when diluted with colloid like hydroxyethyl starches (HES 6%) were not compared when applicated via gelfoam to other methods mentioned before, so no definitive conclusions can show the differences between each of colloids and crystalloids with gelfoam soaked morphine compared to direct morphine application. When we compare our study with other studies we find that the dose of epidural morphine used in our study corresponds to the doses used in earlier studies.…”
Section: Discussionmentioning
confidence: 99%
“…The routine use of surgical gelfoam in the epidural space at the completion of surgery prompted the use of gelfoam as an extended release drug delivery system to prolong the effect of epidural morphine [5]. Earlier studies have compared application of gelfoam soaked in saline with morphine in epidural space to directly applicated morphine [6], but no definitive conclusions can show the differences between each of colloids and crystalloids with gelfoam soaked morphine compared to direct morphine application and for this the present study was designed. Many studies applied colloid in the epidural space either for management of post spinal headache or as epidural volume expansion to augment intrathecal block, and the study by Amira et al [21] was designed to examine the effects of colloid (6% HES) versus normal saline (0.9%) for epidural volume expansion in combined spinal epidural anesthesia for elective cesarean delivery and to assess the quality of block and hemodynamic stability.…”
Section: Introductionmentioning
confidence: 99%
“…The routine use of surgical Gelfoam in the epidural space at the completion of surgery prompted the use of Gelfoam as an extended-release drug delivery system for medications such as morphine 23 and steroids. The rationale for choosing Gelfoam as an extended delivery device is that Gelfoam has the capability to absorb fluid several times its weight.…”
Section: Application Of Triamcinolone Acetonidementioning
confidence: 99%